Mining and validation of est-microsatellites in freshwater prawns, macrobrachium rosenbergii / Shairah Abdul Razak - Abdul Razak, Shairah (2011)

(untitled)
The current study conducted in purpose to illustrate the utility of EST-derived SSR in characterizing wild populations of M. rosenbergii in Malaysia‟s rivers. A novel set of EST-SSR generated from RNA of M. rosenbergii were validated in a full panel of 120 samples from four wild populations through Polymerase Chain Reaction (PCR). Seven EST-SSR loci were identified, characterized, and evaluated on 30 individuals each from the populations namely Negeri Sembilan, Kedah, Sarawak, and Terengganu. The average polymorphic informative content value (PIC) for these seven primers was found to be 0.6208 indicating considerable degree of polymorphism with number of alleles detected ranged from 4 to 10. The observed heterozygosity value count during multi-population analyses ranged from 0.5333 to 0.8333, whilst the expected ranged from 0.6288 to 0.7009. There was no linkage disequilibrium (LD) observed between all pairs of EST-SSRs loci. All loci, except for EST MR8 conformed to the Hardy-Weinberg equilibrium (HWE) suggesting factors violating the neutral expectation such as selection might have caused the locus to deviate from equilibrium. The FIS index demonstrated no indication of inbreeding among individuals of each population. There was evidence that all populations assessed in this study are drawn from a single, large panmictic population; no genetic heterogeneity observed in population structure analysis, estimate of fixation index value in pairwise comparisons among the four localities revealed very low magnitude of differentiation (FST ranged between 0.00888 to the highest of 0.10644). iii The results indicated that these polymorphic EST-SSR derived from M. rosenbergii would be useful for population genetic structure analysis and genetic diversity assessment in prawn populations as part of management policies of natural resources to ensure sustainability of wild broodstock for future development of prawn culture industries.